ANALISIS PERANAN CUSTOMER SERVICE DALAM MANAJEMEN KOMPLAIN CARD ATM (STUDI KASUS BSI KC PADANG IMAM BONJOL) - Wulanda Putri Widy; Sandra Dewi (Jurnal Ekonomi dan Bisnis, 2024)
The background to this research is to look at the role of customer service in managing ATM card complaints so that it can retain old customers and new customers to continue making transactions at BSI Bank KC Padang Imam Bonjol. The purpose of this research is to describe the role of Customer Service in ATM Card Complaint management. The role of Customer Service in Management of ATM Card complaints at BSI KC Padang Imam Bonjol has been implemented according to the SOP, namely serving customers by always giving a greeting and smile, providing good service to maintain the Bank's image. The research method used by the author here is qualitative research, with the key research informants being data collection, researchers using observation, interviews and documentation methods. The research results obtained from analyzing the role of Customer Service in managing ATM Card complaints at BSI KC Padang Imam Bonjol are that the role provided by Customer Service is good enough so that Customers feel safe and comfortable when making complaints to Customer Service because Customer Service always responds to customer complaints. quickly and precisely.